2017
DOI: 10.1002/adma.201606572
|View full text |Cite
|
Sign up to set email alerts
|

High‐Energy‐Density Metal–Oxygen Batteries: Lithium–Oxygen Batteries vs Sodium–Oxygen Batteries

Abstract: The development of next-generation energy-storage devices with high power, high energy density, and safety is critical for the success of large-scale energy-storage systems (ESSs), such as electric vehicles. Rechargeable sodium-oxygen (Na-O ) batteries offer a new and promising opportunity for low-cost, high-energy-density, and relatively efficient electrochemical systems. Although the specific energy density of the Na-O battery is lower than that of the lithium-oxygen (Li-O ) battery, the abundance and low co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(105 citation statements)
references
References 167 publications
(327 reference statements)
0
105
0
Order By: Relevance
“…Therefore, in spite of the enormous energy density of Li-O 2 batteries (11140 Wh kg Li −1 and 3456 Wh kg Li2O2 −1 ), its practical application or commercialization has been continuously delayed due to the poor energy efficiency arising from the irreversible decomposition of insulating Li x O y during electrochemical cycling. [18,19] Thus, the secured catalyst surface looks more important in Li-O 2 batteries not only for alleviating ORR/OER overpotentials but also for guiding the catalytic growth dynamics of Li x O y to maintain the proper interfaces for ions or electron transfer. [20][21][22][23] Song et al demonstrated that the anisotropic Pt-incorporated Li-O 2 cells show unprecedentedly superior energy efficiency up to 87% and stable cyclic retention thanks to the {411} facets with strong O-binding energy and high surface energy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in spite of the enormous energy density of Li-O 2 batteries (11140 Wh kg Li −1 and 3456 Wh kg Li2O2 −1 ), its practical application or commercialization has been continuously delayed due to the poor energy efficiency arising from the irreversible decomposition of insulating Li x O y during electrochemical cycling. [18,19] Thus, the secured catalyst surface looks more important in Li-O 2 batteries not only for alleviating ORR/OER overpotentials but also for guiding the catalytic growth dynamics of Li x O y to maintain the proper interfaces for ions or electron transfer. [20][21][22][23] Song et al demonstrated that the anisotropic Pt-incorporated Li-O 2 cells show unprecedentedly superior energy efficiency up to 87% and stable cyclic retention thanks to the {411} facets with strong O-binding energy and high surface energy.…”
Section: Introductionmentioning
confidence: 99%
“…A breakthrough in increasing the battery energy density requires developing new electrochemical reactions. [83][84][85][86][87][88][89] Along this line, new battery systems have been intensively pursued in recent years, including Li metal batteries, [90][91][92][93][94][95][96] metal-sulfur batteries, 97-104 metal-air (or metal-oxygen) batteries, [105][106][107][108][109] and batteries involving monovalent (eg, Na and K) [110][111][112][113][114][115] or multivalent (eg, Mg, Ca, Zn, and Al) elements/cations. 116 Among various new battery systems, Li-sulfur, Li metal, and Li-oxygen batteries have gained great attraction due to their exceptionally high energy density (Figure 11).…”
Section: Increasing Energy Densitymentioning
confidence: 99%
“…As shown in Figure , most metal anodes in these non‐Li metal–O 2 batteries can offer wide voltage windows and high specific capacities, and thus satisfactory energy densities to meet various requirements. Specially, these metal–O 2 batteries with low‐cost alkali metals (e.g., Na and K) demonstrate comparable volumetric energy density to that of Li–O 2 batteries, while those metal–O 2 batteries with some cheap and safe multivalence elements (e.g., Mg, Zn, and Al) even exhibit superior theoretical volumetric energy densities to the Li‐based ones, which offers great potential for future large‐scale applications.…”
Section: Non‐li Metal–o2 Batteries Versus Li–o2 Batteriesmentioning
confidence: 99%